Psychological and emotional impact of harassment at workplace: a comprehensive examination of its consequences and remediation strategies - Shahid, Fawzia; Jehan, Talat; Termizi, Mazbah; Jaafar Sidek, Mohd Farid; Mohamed, Luqman Hafidz; Mat Russ, Nazirah; Mat Ripin, Faizal Hazri (Zes Rokman Resources, 2023)
Sexual harassment at the workplace has been widely discussed in scientific literature and socio-political organizations for past several years now. Multiple studies have focused on this aspect to support experimental research, dissemination, and preventive measures concerning sexual harassment at the workplace. This has led to a growing awareness among organizations and stakeholders on the significance of addressing and combating sexual harassment at the workplace. Although social scientists have documented a negative association between sexual harassment at the workplace and mental health (i.e., psychological, and emotional), limited research has been carried out on the psychological and emotional repercussions of workplace sexual harassment on women employees. By further probing into the distinct psychological and emotional outcomes of such experiences, this research intends to enhance the understanding of the multi-faceted consequences of sexual harassment on women employees. A survey research strategy was designed to derive the quantitative data through a questionnaire distributed through social media, e-mail, in-person distribution, and WhatsApp groups. Furthermore, the data collected from 255 respondents were then analysed using SPSS (Statistical Package for the Social Sciences) version 2019 including frequency, percentage, median, and standard deviation. The result indicated several consequences due to sexual harassment in the workplace such as fear and paranoia (58%), sleep disturbances (55%), anxiety (46%), low self-esteem (46%), depression (43%), decreased job satisfaction (39%), post- traumatic stress disorder (39%), and interpersonal difficulties (38%). Additionally, it is important to address such behaviours through effective remediation strategies to provide the victims with the needed assistance and coping mechanisms. The result revealed that the majority of the respondents prefer to talk to their family or friends with the highest percentage (29%), followed by seeking professional help (11%) and engaging in hobbies (8%). The results were expected to provide valuable insights into developing practical and evidence-based interventions that organizations can implement to create safer and healthier work environments, especially for women employees.